Temasik: Between Convention and Invention - Che Man, Siti Hajar (Malay Literature, 2014)
This article focusses on the issue of style of presentation by some Singapore short story writers on the livelihood among the Singapore society in the era of `65 leading to the early 90's. Temasik (short story anthology by Singapore writers) published by the Language and Literary Institute in 1987 and edited by Suratman Markasan is chosen for the purpose. Each and every short story in this anthology portrayed the what, where, who, how and when of the Singapore society after 1965 which later became the rigours of livelihood till today. The issues touched upon by the writers are analysed based on the existence of the inter-relation of two dimensions - namely the concept of the creation of creative works and the observation of its continuity and layering between invention and convention. The first concept deals with the bond between reality, imagination, illusion and fantasy whereas the second concept deals with the combination between the pattern of story telling which also mirrors the maturity and experience of the short story writers of the 80's. The Temasik anthology is not only seen as a catalyst, but also as an impetus toward the production of creative works of quality, apart from ushering the emergence of Singapore writers and works in the era of e-literature. Keywords : Temasik , creative works, convention, invention, e-literature